How does topography affect wind abrasion on Mars? Recently observed shifts in ventifact orientation at Gale crater - Daniel Y. Zhou; Madison L. Turner; William Rapin; Juergen Schieber; Amelie L. Roberts; Aster C. Cowart; Megan E. Hoffman; Bernard Hallet; Steve G. Banham; Deirdra Fey; Kevin W. Lewis; Sanjeev Gupta; et al. (Icarus, 2025)

Hypotheses for the water and metal fluxes to the rippled Amapari Marker Band, Gale Crater, Mars - E.S. Kite; P. Gasda; C.J. Tino; C. Weitz; L. Thompson; B.M. Tutolo; C.A. Mondro; W.H. Farrand; S. Gupta; J. Schieber; W.E. Dietrich; N. Mangold; et al. (Earth and Planetary Science Letters, 2025)

Cold Surface Waters of the Sub‐Antarctic Pacific Ocean Support High Cyanophage Abundances and Infection Levels - Camelia Shopen Gochev; David Demory; Adriana Lopes dos Santos; Michael C. G. Carlson; Andrés Gutiérrez‐Rodríguez; Joshua S. Weitz; Debbie Lindell (Environmental Microbiology, 2025)
Cyanobacterial distributions are shaped by abiotic factors including temperature, light and nutrient availability as well as biotic factors such as grazing and viral infection. In this study, we investigated the abundances of T4‐like and T7‐like cyanophages and the extent of picocyanobacterial infection in the cold, high‐nutrient‐low‐chlorophyll, sub‐Antarctic waters of the southwest Pacific Ocean during austral spring. Synechococcus was the dominant picocyanobacterium, ranging from 4.7 × 10 3 to 1.2 × 10 5 cells∙mL −1 , while Prochlorococcus abundances were relatively low overall, ranging from 1.0 × 10 3 to 3.9 × 10 4 cells∙mL −1 . Using taxon‐specific, single‐virus and single‐cell polony methods, we found that cyanophages were on average 15‐fold, and up to 50‐fold, more abundant than cyanobacteria in these waters. T4‐like cyanophages (ranging from 1.7 × 10 5 to 6.5 × 10 5 phage·mL −1 ) were 2.7‐fold more abundant than T7‐like cyanophages (ranging from 3.1 × 10 4 to 2.8 × 10 5 phage·mL −1 ). Picocyanobacteria were primarily infected by T4‐like cyanophages with more Synechococcus (4.8%–12.1%) infected than Prochlorococcus (2.5%–6.2%), whereas T7‐like cyanophages infected less than 1% of both genera. These infection levels translated to daily mortality in the range of 5.7%–26.2% and 2.9%–14.3% of the standing stock of Synechococcus and Prochlorococcus , respectively. Our findings suggest that T4‐like cyanophages are significant agents of cyanobacterial mortality in the cold, low‐iron, sub‐Antarctic waters of the South Pacific Ocean.

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Lab-made 3D printed electrochemical sensors coupled with chemometrics for Brazilian coffee authentication - Yhan S. Mutz; Denes do Rosario; Luiz R.G. Silva; Diego Galvan; Jéssica S. Stefano; Bruno C. Janegitz; David A. Weitz; Patricia C. Bernardes; Carlos A. Conte-Junior (Food Chemistry, 2023)

Weather underground: Subsurface hydrologic processes mediate tree vulnerability to extreme climatic drought - Blair C. McLaughlin; Rachel Blakey; Andrew P. Weitz; Xue Feng; Brittni J. Brown; David D. Ackerly; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2020)
Drought extent and severity have increased and are predicted to continue to increase in many parts of the world. Understanding tree vulnerability to drought at both individual and species levels is key to ongoing forest management and preparation for future transitions in community composition. The influence of subsurface hydrologic processes is particularly important in water‐limited ecosystems, and is an under‐studied aspect of tree drought vulnerability. With California's 2013–2016 extraordinary drought as a natural experiment, we studied four co‐occurring woodland tree species, blue oak ( Quercus douglasii ), valley oak ( Quercus lobata ), gray pine ( Pinus sabiniana ), and California juniper ( Juniperus californica ), examining drought vulnerability as a function of climate, lithology and hydrology using regional aerial dieback surveys and site‐scale field surveys. We found that in addition to climatic drought severity (i.e., rainfall), subsurface processes explained variation in drought vulnerability within and across species at both scales. Regionally for blue oak, severity of dieback was related to the bedrock lithology, with higher mortality on igneous and metamorphic substrates, and to regional reductions in groundwater. At the site scale, access to deep subsurface water, evidenced by stem water stable isotope composition, was related to canopy condition across all species. Along hillslope gradients, channel locations supported similar environments in terms of water stress across a wide climatic gradient, indicating that subsurface hydrology mediates species’ experience of drought, and that areas associated with persistent access to subsurface hydrologic resources may provide important refugia at species’ xeric range edges. Despite this persistent overall influence of the subsurface environment, individual species showed markedly different response patterns. We argue that hydrologic niche segregation can be a useful lens through which to interpret these differences in vulnerability to climatic drought and climate change.

Low-Intensity Ultrasound Modulates Ca2+ Dynamics in Human Mesenchymal Stem Cells via Connexin 43 Hemichannel - Chi Woo Yoon; Hayong Jung; Kyosuk Goo; Sunho Moon; Kweon Mo Koo; Nan Sook Lee; Andrew C. Weitz; K. Kirk Shung (Annals of Biomedical Engineering, 2018)

Building reactive copper centers in human carbonic anhydrase II - He Song; Andrew C. Weitz; Michael P. Hendrich; Edwin A. Lewis; Joseph P. Emerson (JBIC Journal of Biological Inorganic Chemistry, 2013)